Kepatuhan Wartawan Terhadap Kode Etik Jurnalistik Di Kota Palangka Raya: Journalists ' Compliance With The Code Of Journalistic Ethics In The City Of Palangka Raya - Hidayat, Rahmat (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2016)
This research aims to determine what are the most common problems in the world of the journalistic code of ethics so that it can be a good picture of the press and uphold the rules of the press. Methods that Used in relation to this research, then the research Debitor is used using a qualitative approach by using the adulteration of primary data sources and secondary data sources. Primary data sources obtained by interviews to journalists are always insurers who perform journalistic tasks in the field of observations while the data sources of the Sukender legislation, code of Journalism Ethics, official documents, Books and tangible research results report the data materials in this study. The results of this scientific journal can be proved by the interview among journalists in the city of Palangka Raya who claimed to still be able to work and understand the implementation of the Code of journalistic ethics, specifically articles relating to independence Of the press in carrying out its work. In conclusion, in the world of the press itself still, need some improvement in addition to providing training to journalists but also strengthening the structure and ability of the press agencies themselves in Indonesia.